Santri's Economic Empowerment Model in Pesantren Al-Ittifaq Ciwidey District of Bandung - Arip Syaprudin (UIN Sunan Gunung Djati Bandung, 2017)
Pesantren is a live episode that combines various life skills, not least agriculture. Various activities of life in pesantren have encouraged the sense of ideology of Santri. Educational activities that essentially the learning process requires thinking as a strong foundation so that the implementation of education that becomes the duty of his duties performed with a solid and really can be accounted for. This research uses descriptive qualitative, research place at Pesantren Al-Ittifaq Ciwidey district of Bandung. The subject of this research is Santri in pesantren while the informant is the Kiai or Ustādh. Data collection techniques use observation, interview, and documentation. I am checking the validity of the data using triangulation. Data analysis uses data reduction, data presentation, and conclusion. Based on the result of the research, it can be concluded that the model of empowering students at Pesantren Al-Ittifaq that is by the establishment of Core Management Unit Agribusiness, - effective practice in the field, establishing the Agribusiness Incubator Center, cooperating with various institutions and institutions, forming Santri agribusiness groups.